Political Background of Islamic Educational Institutions and the Reach of the Stage in Southeast Asia - Takeshi Kohno (Studia Islamika, 2009)
The school taught terrorisms this paper asserts that examining madrasahs in the context of "the war on terrors' point of view misses the real undercurrent of social transformation that is currently going on in educational institutions in Southeast Asia: the battle for control of education between the state and society. It also claims that this battle, which is not unusual in the process of nation-state building in post-colonial states, has a renewed meaning because of the age of the war on terror. In other words, the key assertion is that the current transformation of Islamic schools in Southeast Asia should be viewed within the context of the state-building process, or the state's attempts to control Islamic education. What's more is that the "the war on terror" is being treated as an opportunity by both sides to take control of the educational transformation processes.DOI: 10.15408/sdi.v16i2.480